2002
DOI: 10.1002/cne.10414
|View full text |Cite
|
Sign up to set email alerts
|

AMPA glutamate receptor subunits in the guinea pig hypothalamus: Distribution and colocalization with progesterone receptor

Abstract: Excitatory amino acids (EAAs), particularly glutamate, have been implicated in the control of luteinizing hormone (LH) secretion through facilitation of gonadotropin-releasing hormone release. The effects of EAAs are mediated by means of ionotropic glutamate receptors, which are divided into N-methyl-D-aspartate (NMDA) and non-NMDA (kainate and AMPA) subtypes. Moreover, ovarian steroids are responsible for inducing the preovulatory surge of LH and are involved in the actions of EAAs on LH release. Progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
(92 reference statements)
0
5
0
1
Order By: Relevance
“…In terms of the progesterone receptor, only one study appeared to show possible interactions with glutamate. This study demonstrated that AMPA receptor colocalized with the progesterone receptor in guinea pig hypothalamus (Warembourg and Leroy, 2002).…”
Section: Potential Role Of Glutamate In Steroid-independent Female Sementioning
confidence: 51%
“…In terms of the progesterone receptor, only one study appeared to show possible interactions with glutamate. This study demonstrated that AMPA receptor colocalized with the progesterone receptor in guinea pig hypothalamus (Warembourg and Leroy, 2002).…”
Section: Potential Role Of Glutamate In Steroid-independent Female Sementioning
confidence: 51%
“…In addition, the observed fluctuation in AMPA binding densities could be a result of an AMPA receptor translocation from intracellular inactive stores specially known for this receptor (Kullmann, 1994;Hall and Soderling, 1997) to the cell surface, where it becomes functional (Hall and Soderling, 1997;Shi et al, 1999). Moreover, variations in AMPA receptor densities could also be due to estradiol-induced changes in progesterone receptor densities, since a colocalization of AMPA receptor subunits and the progesterone receptor has recently been described in the guinea pig brain (Warembourg and Leroy, 2002). These known rapid AMPA receptor fluctuations indicate that AMPA receptor densities are more variable than the NMDA receptor system.…”
Section: Discussionmentioning
confidence: 88%
“…AMPA type glutamate receptor mediates rapid excitatory synapse transmission, which is mainly permeable for Na þ , rather than Ca 2þ (Zhang et al 2006). Warembourg and Leroy (2002) reported that essential amino acid, particularly glutamate, was implicated in the control of luteinizing hormone (LH) secretion through facilitation of gonadotropin-releasing hormone release. LH mainly promotes Leydig cells of the adult testis to synthesize testosterone.…”
Section: Discussionmentioning
confidence: 99%